Prospective cohort study of the association between early lactation mastitis and the presence of sole ulcers in dairy cows. (5th February 2022) - Watson, Christopher; Barden, Matthew; Griffiths, Bethany E.; Anagnostopoulos, Alkiviadis; Higgins, Helen M.; Bedford, Cherrill; Carter, Stuart; Psifidi, Androniki; Banos, Georgios; Oikonomou, Georgios
Abstract: Background: The objective of this study was to investigate the association between (sub)clinical mastitis (CM) in the first 30 days in milk (DIM) and the presence of sole ulcers (SU) later in lactation. Methods: Holstein cows and heifers were examined for presence of sole haemorrhage and SU before calving, in the first 14 days postcalving and in early lactation (after 30 DIM). CM episodes and somatic cell counts (SCC) measurements were obtained from farm records. Multivariable logistic regression was used for data analysis. Results: Odds of SU in early lactation were 2.44 times greater (95% confidence interval [CI] 0.97–5.54) in cows that had CM in the first 30 DIM compared to cows that did not have CM in the first 30 DIM. When cows that had SU precalving or at the calving check were excluded from the dataset, an association of CM in the first 30 DIM with later presence of SU was no longer statistically significant but the same numeric trend still existed (odds ratio [OR] 2.25, 95% CI 0.81–5.34). The odds of SU in early lactation were 1.70 times greater in cows that had high SCC compared to cows that did not have high SCC in the first 100 DIM (95% CI 1.13–2.55). Conclusion: An association was found between CM in the first 30 DIM and presence of SU in early lactation (after 30 DIM). Elucidating the mechanism behind this relationship could improve our understanding of the aetiopathogenesis of both diseases and lead to new preventive strategies.